THE EFFECT OF MOBILE BANKING ON THE PERFORMANCE OF BANKS LISTED ON INDONESIA STOCK EXCHANGE (IDX) - Jauhari, Harris
The number of internet users and the number of smartphone users in Indonesia have increased quite significantly in the past few years. In addition, the number of mobile banking users for several banks in Indonesia has increased from 2015 to 2019. The growth that has occurred has made mobile banking one of the products of electronic banking which is currently a major concern for the banking industry in Indonesia.